Development of a registry to evaluate immobilized lipase cartridge use in pediatric patients with short bowel syndrome/intestinal failure - Jason Soden; Megan Aarnio-Peterson; Justin Neal; David P. Recker; Ann E. Remmers (Intestinal Failure)
Background: Over the past 4 years, outpatient use of an immobilized lipase cartridge (ILC) (RELiZORB®; Alcresta Therapeutics) in pediatric patients with intestinal failure (IF) and short bowel syndrome (SBS) has increased. Although ILC use has been associated with improved fat absorption and enteral feeding tolerance in patients with exocrine pancreatic insufficiency and cystic fibrosis, there are no published reports of ILC use in patients with IF. Materials and methods: This prospective direct-to-patient observational registry collects real-world data regarding medical history, growth, quality of life, and progression towards enteral autonomy in pediatric patients with IF/SBS receiving enteral nutrition administered through an ILC. Eligible patients identified by a registry clinical coordinator are given the option to enroll in the registry. Data collected for the registry includes caregiver-as-proxy patient-reported outcome questionnaires, and clinical data from routine clinic visits for each patient for up to one year. A Registry Steering Committee provides oversight and reviews the scientific merit of proposals for subsequent data analysis. Results: The registry received Institutional Review Board approval in July 2024 with enrollment commencing shortly thereafter. As of October 11, 2024, 41 patients receiving care at 25 institutions in the United States were enrolled in the registry. Conclusion: It is anticipated that data collected through this registry will allow study of relevant research questions related to ILC use in patients with IF/SBS, including queries related to growth, progression towards enteral autonomy, and quality of life.